Sobralia aryaelizabethiana (Orchidaceae), a small and unusual new species from northern Peru - Ocupa-Horna, Luis (2025)
A new species of Sobralia from the Andes of northern Peru is described and illustrated. Sobralia aryaelizabethiana can be easily recognized by its short stems with axillary racemose inflorescences. The species is most similar to S. rigidissima but differs in having smaller leaves (up to 8 cm vs. 15 cm), oblanceolate sepals up to 29 mm long (vs. linear-oblong, up to 13 mm), and an unlobed, ovate lip (vs. trilobed, cuneate-flabellate). Additionally, it has longer petals, widely ovate floral bracts with a triangular apex, and lavender flowers with purplish lip stains (vs. rose-colored with a white lip). Sobralia aryaelizabethiana is found only in a small area near Abra de Porcuya in the Piura department, on northwestern Peru. It thrives in semiarid soils that are partially covered with herbaceous or shrubby vegetation. This species is adapted to an environment characterized by intense sunlight and the constant air currents that bring in dense fog. The species diversity of Sobralia in Peru remains incompletely understood and a comprehensive taxonomic revision is required to clarify its richness.